Note: Focus error detection device for thermal expansion-recovery microscopy (ThERM) - Domené, Esteban Alejo (2013)
An innovative focus error detection method is presented that is only sensitive to surface curvature variations, canceling both thermoreflectance and photodefelection effects. The detection scheme consists of an astigmatic probe laser and a four-quadrant detector. Nonlinear curve fitting of the defocusing signal allows the retrieval of a cutoff frequency, which only depends on the thermal diffusivity of the sample and the pump beam size. Therefore, a straightforward retrieval of the thermal diffusivity of the sample is possible with microscopic lateral resolution and high axial resolution (∼100 pm).